Metaverse Awareness of Turkish Generation Z Preservice Teachers - Akpinar, Burhan; Kuloğlu, Ayşenur; Erdamar, Fatih Selim (My University, 2022)
The aim of this study was to examine the metaverse awareness of Turkish Generation Z pre-service teachers with regard to several variables. A total of 1048 pre-service teachers born after 2000 participated in the study in which the descriptive survey model was used. The data were collected through a questionnaire and analyzed using descriptive statistical techniques. The findings revealed that the participants had low metaverse awareness and experience of this technology. Differing from the global Generation Z, they perceived the metaverse more in the context of game and entertainment. The participants thinking that the metaverse is partially beneficial for education emphasized its role as a technological tool that supports education rather than the role of the metaverse as an educational ecosystem itself. This finding may be related to the fact that the Turkish Generation Z preservice teachers were not fully aware of the virtual and digital technology phenomenon such as the metaverse and they were not aware of its educational potential. The low awareness of the T Turkish Generation Z preservice teachers about the metaverse can be considered as a deficiency in terms of compliance of the Turkish Education System with the Information Age. It was concluded as a result of this study that the awareness of Turkish Generation Z preservice teachers, who differ from their global counterparts in some features, about virtual and digital technology is not yet ready for the transformation of Turkish Education System to into a completely virtual and digital form. Thus, this unity should be ensured through intermediate forms such as the Hybrid Model.
Keywords: Metaverse; Turkish Generation Z; Generation Z Preservice Teachers; Metaverse and Education